Interest Rates and Exchange Rates in Normal and Crisis Times - Caterina Forti Grazzini; Malte Rieth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
The paper studies the relation between the US-Dollar/Euro exchange rate and US and euro area interest rates during normal and crisis times. We describe each asset price within a multifactor model and identify the causal contemporaneous relations through heteroskedasticity. We find that US rates and macroeconomic conditions dominate exchange rate and interest rate movements before and during the global financial crisis, while this pattern sharply reverses during the European debt crisis.
Keywords: E44; F31; G1; 330